ANALISIS MALWARE ANDROID MENGGUNAKAN METODE REVERSE ENGINEERING - Frenvol De Santonario Magno Moises; Joko Dwi Santoso (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Abstract: apid progress has been made in the development of Android-based smartphone technology. Communication, shopping and financial transactions are just a few of the daily tasks that people perform with their smartphones. Android, on the other hand, is an open-source operating system that makes it easy for anyone to create Android apps that can be accessed via a smartphone. Counting applications embedded with malware by application, one of which is malware.The analysis was carried out with samples of Trojan malware in the syssecApp.apk application using the reverse engineering method. in doing Trojan malware reverse engineering using APKTOOL tools, JD-GUI.This research will analyze the syssecApp.apk application that infects Trojan malware using the reverse engineering method. The results of the analysis on the syssecApp.apk application found that there is an ip host receiver contained in the source code in syssecApp.apk